Economics of electricity grid interconnections: A heterogeneous markets' design context - Anas Damoun; Rahmatallah Poudineh (The Oxford Institute for Energy Studies, 2025)
Heterogeneous interconnections, which link regulated electricity markets to liberalised ones, are becoming increasingly important. Several such interconnections are set to be established in the near future especially between European and North African countries (e.g., Tunisia-Italy, Egypt-Cyprus-Greece, Algeria-Italy), in addition to various already existing ones. These interconnections present unique challenges and peculiarities that are not adequately addressed in the existing literature, which often focuses on homogeneous interconnections (i.e., those linking liberalised markets). Understanding the economics of heterogeneous interconnections becomes crucial for enabling clean energy trade between markets at different development stages. The capacity allocation mechanisms for heterogeneous interconnections often appear to be adaptations of those used in homogeneous interconnections which does not account for the unique challenges of heterogeneous contexts. In this paper we show that the regulated market has an informational advantage over the liberalised market, as it can observe both actual and historical prices in the liberalised market, as well as the aggregate supply and demand curves that determine them. It can therefore leverage its informational advantage to manipulate outcomes by misrepresenting its marginal costs and their sensitivity to cross-border exchange. As a result, heterogeneous interconnections are likely to be less efficiently utilised compared to homogeneous ones, reducing overall welfare but increasing the regulated market's individual welfare. This implies that mechanisms that decentralise exchange decisions and disregard congestion revenues (e.g., implicit auctions) are less effective in heterogeneous contexts where the regulated market's utility can monopolise arbitrage decisions. The inefficiencies in heterogeneous interconnections can be reduced by implementing appropriate allocation mechanisms and policies. For example, mechanisms that enable potential private agents in the regulated market to independently carry out cross-border operations or those that enable dispatching cross-border exchange further from delivery could be effective. Similarly, long-term cross-border contracts for energy could be negotiated to ensure a minimum utilisation level of the interconnection and reduce the manipulation margin.
Keywords: 330; capacity allocation; electricity market design; implicit auctions; interconnections; liberalised electricity market; market coupling; regulated electricity market